AVK game model based on technology and local wisdom to improve physical fitness of children aged 6-12 years - Megariani, Evi; Handayani, Widya; Putri, Siti Ayu Risma; Lestari, Hikmah; Lanos, Muhsana El Cintami (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2026)
This study aims to develop and evaluate AVK (Audio, Visual, Kinesthetic) Game Models based on Technology and Local Wisdom to improve the physical fitness of children aged 6-12 years. The research was carried out for one year using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The analysisstage involved identifying learning needs, dominant learning styles, and the physical fitness conditions of children through observations, interviews, and surveys involving 100 student participants. The design and development stage resulted in four interactive games that integrate physical movement, audio-visual media, and elements of South Sumatra local culture, namely Musi Fort, Palace Jump Rope, Sriwijaya Hide and Seek, and Belida Fish Catch. The design and development stage produced four interactive games that combine physical movement, audio-visual media, and elements of local South Sumatra culture: Musi Fort, Palace Jump Rope Jump, Sriwijaya Hide and Seek, and Belida Fish Catch. The implementation of the model was carried out on 60 students (consisted of 30 males and 30 females), with pretest and posttest measurements of physical fitness using TKSI instruments, as well as observation of student involvement and response. The evaluation stage was conducted after implementation by comparing pre-test and post-test results, supported by observations and questionnaires on students’ and teachers’ responses, with the evaluation results serving as the basis for drawing conclusions regarding the effectiveness and feasibility of the model in elementary school Physical Education learning. The results of the statistical analysis using a paired-sample t-test showed a significant difference between the pre-test and post-test scores (p < 0.05). The results showed significant improvements in various aspects of physical fitness, namely flexibility (10%), muscle endurance (8%), coordination (10%), agility (8%), and cardiopulmonary endurance (9%). In addition, 91% of students showed a positive response to this learning model, and teachers considered this media to be effective and support the integration of local wisdom values. In conclusion, the AVK Game Model based on Technology and Local Wisdom has been proven to be effective in improving physical fitness, motivating students’ active participation, and strengthening appreciation for local culture. This model deserves to be used as an innovative alternative in Physical Education learning in elementary schools, which brings together technology, multiple intelligences, and local wisdom values in a fun and contextual way.